Highly selective nickel ethylene oligomerization catalysts based on sterically hindered tris(pyrazolyl)borate ligands - Kunrath, F. A.; de Souza, R. F.; Casagrande, O. L.; Brooks, N. R.; Young, V. G. (Amer Chemical Soc, 2003)
The reaction of TlTp' (Tp' = HB(3-mesitylpyrazolyl)(3)(-) (Tp(Ms)), HB(3-mesitylpyrazolyl)(2)(5-mesitylpyrazolyl)(-) (Tp(Ms)*)) with NiCl(2).6H(2)O affords Tp(Ms)NiCl (1) and Tp(Ms)*NiCl (2) in good yield. The compound 2 undergoes an isomerization process to form [{Tp(Ms)**}NiCl](2) (3) (Tp(Ms)** = HB(5-mesitylpyrazolyl)(2)(3-mesitylpyrazolyl)(-)) in 68% yield. Treatment of the tris(pyrazolyl)-borate nickel compounds 1 and 2 with alkylaluminum cocatalysts such as methylalumoxane (MAO) and trimethylaluminum (TMA) in toluene generates active catalysts for ethylene oligomerization. The compound 1 shows turnover frequencies in the range of (2.2-43.1) x 10(3) h(-1). Oligomerization reaction conditions can be adjusted that lead to selectivities as high as 81% for butene-1.